The Future of Nigeria’s Economic Development: Implication of Domestic Debt Dynamics - Ikwor, Uwakwe; Elom, Joseph; Ikwuo, Ama; Nworie, Gilbert (PT ARRUS Intelektual Indonesia, 2025)
The study examined the effect of domestic debt on economic development in Nigeria. Specifically, the study examined the effect of ways and means loan, treasury bills and treasury bond on human development index. The research adopted ex-post facto research design. Secondary data were collected from Debt Management Office, National Bureau of Statistics and Central Bank of Nigeria Statistical Bulletin spanning from 2000 to 2023. The econometric technique of Dynamic Least Squares, Augmented Dicky Fuller, Unit Root Test, and Johansen Co-integration test were employed in the data analysis. It was found that ways and means loans and treasury bonds have significant positive effect on economic development in Nigeria while treasury bills have a negative but non-significant effect on economic development in Nigeria. By implication, when long-term debt instrument is properly utilized, it brings about positive development. Therefore, the study recommended that the National Assembly must take its oversight responsibilities more seriously and ensure that Ways and Means loans are strictly allocated to productive, growth-enhancing expenditures. This is essential to avoid fueling inflation and triggering macroeconomic instability. Strengthening fiscal discipline through vigilant oversight will help safeguard the economy while promoting sustainable development.